Survival rate of antitumour necrosis factor‐α treatments for psoriasis in routine dermatological practice: a multicentre observational study. (30th August 2013) - Esposito, M.; Gisondi, P.; Cassano, N.; Ferrucci, G.; Del Giglio, M.; Loconsole, F.; Giunta, A.; Vena, G.A.; Chimenti, S.; Girolomoni, G.
Abstract : What's already known about this topic? Very few studies have analysed long‐term efficacy and safety of antitumour necrosis factor (anti‐TNF)‐α agents in plaque psoriasis. Treatment adherence is an overall marker of treatment success, and it depends on multiple factors including efficacy, safety, patients' satisfaction and dermatologists' confidence with the treatment. Survival rate is a standardized method for estimating treatment adherence. What does this study add? Adherence to anti‐TNF‐α agents after 2 years was > 70%. The risk of drug discontinuation was significantly higher in women than in men, in case of treatment with adalimumab and infliximab compared with etanercept, and in patients who required a traditional systemic treatment as a rescue therapy, compared with patients treated exclusively with TNF‐α blockers. Summary: Background: Adherence is an overall marker of treatment success, and it depends on multiple factors including efficacy and safety. Despite the wide use of tumour necrosis factor (TNF)‐α blockers in the treatment of plaque‐type psoriasis, few data regarding treatment adherence in routine clinical practice are available. Objectives: To estimate the long‐term survival rate of anti‐TNF‐α therapy in a cohort of patients with psoriasis in routine clinical practice; to evaluate the reasons for and predictors of treatment discontinuation. Methods: The Outcome and Survival rate Concerning Anti‐TNF Routine treatment (OSCAR) study was based on a retrospective analysis to estimate the long‐term survival rate of the first anti‐TNF‐α treatment in patients with psoriasis, from three Italian academic referral centres. Adult patients ( n  =   650) with plaque psoriasis treated with a first course of adalimumab, etanercept or infliximab for ≥ 3 months were included. Results: Global adherence to anti‐TNF‐α treatments after 28·9 ± 15·4 months (867 ± 462 days) of observation was 72·6%. Etanercept showed a longer survival (mean 51·4 months, 1565 days; P  <   0·001) compared with infliximab (36·8 months, 1120 days) and adalimumab (34·7 months, 1056 days). Treatment discontinuation due to primary and secondary inefficacy was observed in 5·2% and 14·5% of patients, respectively, whereas discontinuation due to adverse events was reported in 29 subjects (4·5%). Independent predictors of treatment withdrawal were female gender [hazards ratio (HR) 1·3], treatment with adalimumab or infliximab compared with etanercept (HR 2·7 and 1·7, respectively), and the concomitant use of traditional systemic treatment, as a rescue therapy, compared with monotherapy (HR 1·9). Conclusions: Overall survival of anti‐TNF‐α agents in psoriasis is elevated, with drug discontinuation mostly due to inefficacy. Etanercept showed a longer adherence compared with adalimumab and infliximab.